2001
DOI: 10.1177/153537020222600811
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroepiandrosterone Alters Zucker Rat Soleus and Cardiac Muscle Lipid Profiles

Abstract: High levels of serum free fatty acids (FFA) and lower proportions of polyunsaturated (PU) FAs, specifically arachidonic acid (AA), are common in obesity, insulin resistance (IR), and type 2 diabetes mellitus. Dehydrepiandrosterone (DHEA) decreases body fat content, dietary fat consumption, and insulin levels in obese Zucker rats (ZR), a genetic model of human youth onset obesity and type 2 diabetes. This study was conducted to investigate DHEA's effects on lean and obese ZR serum FFA levels and total lipid (TL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 59 publications
2
10
0
Order By: Relevance
“…By contrast, our experiment spanned a 13-week period that allowed us to observe a significant effect of DHEA on AT composition. Similarly to us, other authors have reported differences in FAs in muscle (Abadie et al 2001), liver (Imai et al 2001), and 3T3-L1 adipocytes (Gómez et al 2002) due to DHEA administration.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…By contrast, our experiment spanned a 13-week period that allowed us to observe a significant effect of DHEA on AT composition. Similarly to us, other authors have reported differences in FAs in muscle (Abadie et al 2001), liver (Imai et al 2001), and 3T3-L1 adipocytes (Gómez et al 2002) due to DHEA administration.…”
Section: Discussionmentioning
confidence: 75%
“…There is a previous work that reported no changes in rat AT fatty acids after 7 days of DHEA administration (Abadie et al 2001). However, due to the lower lipid turn-over rate of this tissue, a 7-day period may not be long enough to appreciate variations in FA profile in AT.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In contrast, others have suggested a role for DHEA-S treatment in fatmass loss (Nestler et al 1988). Furthermore, DHEA-S plasma levels show a negative correlation with visceral fat distribution in women (Garaulet et al 2000) and its administration seems to improve glucose tolerance (Haffner & Valdez, 1994;Richards et al 2000) and to reduce serum cholesterol and TAG (Macario et al 1999), so ameliorating these features of the metabolic syndrome.In rodents, DHEA has been reported to decrease dietary fat and energy intakes as well as body weight and fat content (Taniguchi et al 1995;Richards et al 1999;Pham et al 2000;Abadie et al 2001;Kajita et al 2003;Ryu et al 2003). However, the mechanisms of action of this hormone on body composition are not yet fully understood, although a role in food intake regulation has been suggested (Shepherd & Clearly, 1984;Abadie et al 1993;Svec et al 1995;Wright et al 1995;Svec & Porter, 1996;Pham et al 2000), or even in the utilisation or storage of ingested energy Mohan et al 1990).…”
mentioning
confidence: 99%